History as Resource: Moral Reckonings with Place and with the Wartime Past in Oro Province, Papua New Guinea. Issue 1 (2nd January 2018) - Stead, Victoria
ABSTRACT: Located in Oro Province, Papua New Guinea, Higaturu Station is a place marked by multiple intersections of violence. Originally established as an Australian colonial headquarters, in 1943 it was the site of execution of 21 local Orokaiva men convicted – by the Australian administration – of treason during the Second World War. Eight years after the executions, the nearby Mount Lamington volcano erupted, killing thousands and devastating Higaturu. Today the place remains uninhabited but laden with memory and meaning, a site of ambivalent moral reckonings both with the colonial past and with the postcolonial present. These moral reckonings, in turn, intersect with peoples' experiences of, and hope for, 'development'. In Oro Province, history is becoming a resource – not unlike gold, or the oil palm plantations that extend across the landscape – which might attract outsiders, and with them forms of wealth and possibilities for realising the good life. Accordingly, Higaturu landowners work to attract outsiders to the site of the eruption and the hangings. At the same time, however, they worry that the outsiders they attract – including anthropologists – will exploit and profit from their history in the ways that so many outsiders have profited from the Province's other resources. Commercial considerations inform these hopes and worries, but the mobilisation of history-as-resource also speaks to other concerns, including about the relationships of insiders and outsiders across time, and the proper attributions of guilt, responsibility, and entitlement within colonial and postcolonial landscapes of remembrance.